George Washington's Revenge : The 1777 New Jersey Campaign and How General Washington Turned Defeat into the Strategy That Won the Revolution /: The 1777 New Jersey Campaign and How General Washington Turned Defeat into the Strategy That Won the Revolution. (2022) - Lefkowitz, Arthur S
No abstract available